1992
DOI: 10.1111/j.1399-3011.1992.tb00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational studies on β‐bend containing a cis peptide unit

Abstract: Conformational studies have been carried out on the X-cis-Pro tripeptide system (a system of three linked peptide units, in the trans-cis-trans configuration) using energy minimization techniques. For X, residues Gly, L-Ala, D-Ala and L-Pro have been used. The energy minima have been classified into different groups based upon the conformational similarity. There are 15, 20, 18 and 6 minima that are possible for the four cases respectively arid these fall into 11 different groups. A study of these minima shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The putative occurrence of a reverse hydrogen bonding between NH i and CO i+x was first described by Toniolo4 and later supported for δ‐turns by a theoretical analysis performed by Nagarajaram et al 22. The present study provides the first general analysis of protein turn structures exhibiting a reverse hydrogen bond that reveals some interesting results.…”
Section: Results and Discussion Particularly With Respect To Differesupporting
confidence: 77%
See 1 more Smart Citation
“…The putative occurrence of a reverse hydrogen bonding between NH i and CO i+x was first described by Toniolo4 and later supported for δ‐turns by a theoretical analysis performed by Nagarajaram et al 22. The present study provides the first general analysis of protein turn structures exhibiting a reverse hydrogen bond that reveals some interesting results.…”
Section: Results and Discussion Particularly With Respect To Differesupporting
confidence: 77%
“…He designated two residue “reverse” hydrogen bonded turns as δ‐turns and three residue “reverse” hydrogen‐bonded turns as ϵ‐turns. The existence of δ‐turns was later supported by theoretical conformational studies on three linked peptide units containing a cis‐Pro by Nagarajaram et al 22. To the best of our knowledge, δ‐turns were never described in proteins and ϵ‐turns have not been detected in proteins or peptides or during theoretical conformational analysis.…”
Section: Introductionmentioning
confidence: 80%
“…For the simplest (terminally protected) sequence ‐Gly‐ L ‐Pro‐, the most favorable backbone torsion angles according to ECEEP calculations were found to be ϕ 2 =173°, ψ 2 =85°, ϕ 3 =−75°, ψ 3 =167°28 (this dipeptide was selected for this study because Gly is the least sterically hindered among coded amino acids, and the Xxx‐Pro tertiary amide function is known to accommodate in the cis ‐conformation relatively often as compared to secondary amides) 1. 19, 21, 26, 3237 Moreover, a stabilization of this turn structure was obtained when the amide torsion angle, ω , was allowed to fluctuate in the range ±10–15°. Interestingly, X‐ray diffraction investigations on medium‐sized lactams revealed that the eight‐membered ring compound of this class (enantholactam) is too small to accommodate a trans ‐amide conformation ( ω =180°) 38.…”
Section: Literature Surveymentioning
confidence: 99%
“…Interestingly, in a previous study in the crystal state by the same group,60 it was shown that the sequentially related cyclopentapeptide cyclo [ L ‐Ala‐ L ‐Pro‐Gly‐ D ‐Phe‐ L ‐Pro], although possessing a conformation at the ‐ L ‐Ala‐ L ‐Pro‐ dipeptide unit close to that of ‐Gly‐ L ‐Pro‐,59 appears not to form the intramolecularly H‐bonded δ‐turn. The authors attributed the absence (or the extremely weak character)32 of the H bond to the steric requirements of the L ‐residue at the left corner position of the putative C 8 conformer. In particular, the ϕ , ψ torsion angles of the Ala residue are found in the region of the left‐handed helix of the Ramachandran map, known to be unfavorable for an L ‐configured residue…”
Section: Literature Surveymentioning
confidence: 99%
“…Initially, residues with ϕ > 0° and non‐ trans peptide bond were excluded. There are 17 PDB instances with 22 observations of cis peptide residues, and Gly, Ile, and Ala are the most frequent residues . In total, 67 PDBs with 114 residues have ϕ > 0°.…”
Section: Resultsmentioning
confidence: 99%